2019
DOI: 10.1242/jcs.222067
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin regulates the migration of mesenchymal stromal cells and their interaction with platelets

Abstract: Mesenchymal stromal cells (MSCs) upregulate podoplanin at sites of infection, chronic inflammation and cancer. Here, we investigated the functional consequences of podoplanin expression on the migratory potential of MSCs and their interactions with circulating platelets. Expression of podoplanin significantly enhanced the migration of MSCs compared to MSCs lacking podoplanin. Rac-1 inhibition altered the membrane localisation of podoplanin and in turn significantly reduced MSC migration. Blocking Rac-1 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 65 publications
2
34
1
Order By: Relevance
“…PDPN has been previously found to bind to CLEC-2 on the platelet surface to induce platelet aggregation [23,35]. However, in this study, we found that TE11A cells completely deficient in PDPN were still able to induce platelet aggregation, with similar aggregation kinetics to the parental cells.…”
Section: Role Of Pdpn In Cellular Phenotype and Platelet Activationcontrasting
confidence: 53%
“…PDPN has been previously found to bind to CLEC-2 on the platelet surface to induce platelet aggregation [23,35]. However, in this study, we found that TE11A cells completely deficient in PDPN were still able to induce platelet aggregation, with similar aggregation kinetics to the parental cells.…”
Section: Role Of Pdpn In Cellular Phenotype and Platelet Activationcontrasting
confidence: 53%
“…This could be due to a failure of infiltrating macrophages to egress from the inflamed liver in a timely fashion. Indeed there is a previously described role for the CLEC-2/podoplanin axis in facilitating the egress of other antigen presenting cells from lymphoid organs 44 and stromal cells from areas of inflammation 45 . Taken together these data suggest that activation of CLEC-2 signalling within platelets by macrophage expressed podoplanin within the acutely injured liver suppresses TNF-α release by those macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…PDPN, a transmembrane mucin-like protein released within EVs [33] , plays a critical role in organ development, cell motility and migration [ 34 , 35 ]. On the other hand, PDPN is also associated with tumour cell invasiveness and migration including glioblastoma [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Origin-specific difference in PDPN expression has been reported for MSC isolated from the bone marrow or umbilical cord [39] . PDPN-dependent migration of MSC is suggested to be regulated by GTPase Rac-1 [35] which is also known to mediate tumour cell migration [40] . Our data reveal PDPN-dependent motility and migration of highly migrating subpopulations across two different classes of SC (MSC and NSC).…”
Section: Discussionmentioning
confidence: 99%